Asymmetric supercapacitors with metal-like ternary selenides and porous graphene electrodes. (June 2016) - Xia, Chuan; Jiang, Qiu; Zhao, Chao; Beaujuge, Pierre M.; Alshareef, Husam N.
Abstract: Asymmetric supercapacitors provide a promising approach to fabricate capacitive energy storage devices with high energy and power densities. In this work, asymmetric supercapacitors with excellent performance have been fabricated using ternary (Ni, Co)0.85 Se on carbon fabric as binder-free positive electrode and porous free-standing graphene film as negative electrode. Owing to their metal-like conductivity ( 1.67×10 6 S m −1 ), significant electrochemical activity, and superhydrophilic nature, our nanostructured ternary nickel cobalt selenides result in a much higher areal capacitance (2.33 F cm −2 at 4 mA cm −2 ), better rate performance and cycling stability than their binary selenide equivalents, and other ternary oxides and chalcogenides. Those hybrid supercapacitors can afford impressive areal capacitance and stack capacitance of 529.3 mF cm −2 and 6330 mF cm −3 at 1 mA cm −2, respectively. More impressively, our optimized asymmetric device operating at 1.8 V delivers a very high stack energy density of 2.85 mW h cm −3 at a stack power density of 10.76 mW cm −3, as well as 85% capacitance retention after 10, 000 continuous charge–discharge cycles. Even at a high stack power density of 1173 mW cm −3, this device still deliveries a stack energy density of 1.19 mW h cm −3, superior to most of the reported supercapacitors. Graphical abstract: Asymmetric supercapacitors with excellent performance have been fabricated using ternary (Ni, Co)0.85 Se on carbon fabric as binder-free positive electrodes and porous free-standing graphene films as negative electrodes. Our optimized asymmetric device operating at 1.8 V delivers a very high stack energy density of 2.85 mW h cm −3 at a stack power density of 10.76 mW cm −3, as well as 85% capacitance retention after 10, 000 continuous charge–discharge cycles. Even at a high stack power density of 1173 mW cm −3, this device still deliveries a stack energy density of 1.19 mW h cm −3, superior to most of the reported supercapacitors. Highlights: A highly conductive ternary nickel cobalt selenide electrode is fabricated for supercapacitor applications. The (Ni, Co)0.85 Se electrodes show much higher areal capacitance and better rate performance than their binary counterparts. Freestanding porous graphene film with excellent supercapacitor performance is successfully prepared. Ultrahigh stack energy and power densities, and outstanding long term cycling stability can be achieved in optimized asymmetric supercapacitor.